The global financial crisis: how similar? How different? How costly? - Stijn Claessens; M. Ayhan Kose; Marco E. Terrones (TÜSİAD-Koç University Economic Research Forum, 2010)
This paper provides a brief analysis of three major questions raised in the context of the recent global financial crisis. First, how similar is the crisis to previous episodes? We argue that the crisis featured some close similarities to earlier ones, including the presence of credit and asset price booms fueled by rapid debt accumulation. Second, how different is it from earlier episodes? We show that, as much as it displayed some similarities with previous cases, it also featured some significant differences, such as the explosion of opaque and complex financial instruments in a context of highly integrated global financial markets. Third, how costly are recessions that followed these types of crises? Although the latest episode took a very heavy toll on the real economy, we argue that this was not a surprising outcome. In particular, historical comparisons indicate that recessions associated with periods of deep financial disruptions result in much larger declines in real economic activity. We discuss the implications of these findings for economic and financial sector policies and future research.
Keywords: E32; E44; E51; F42; 330; Global financial crisis; Similarities; Differences; Cost; Recessions; Finanzmarktkrise; Internationaler Finanzmarkt; Vergleich; Soziale Kosten; Makroökonomischer Einfluss; Welt